Local voting protocol step-size choice for consensus achievement. (2018) - Amelin, Konstantin; Amelina, Natalia; Ivanskiy, Yury; Jiang, Yuming
In the paper, a multi-agent network system of different computing nodes is considered. A problem of load balancing in the network is addressed. The problem is formulated as consensus achievement problem and solved via local voting protocol. Agents exchange information about their states in presence of noise in communication channels. For the system operating in noised conditions analytically obtained estimation of control protocol optimal step size value is given. The dependence of the system behaviour on value of control protocol step-size is demonstrated in simulation examples.